“The only girl in such a big class”: Women Students at the University of Toronto’s Faculty of Applied Science and Engineering during the 1920s and the 1930s - Heap, Ruby (Scientia Canadensis, 2006)
AbstractThis article draws the collective profile and examines the experiences of the handful of women who formed the first generation of female students enrolled at the University of Toronto's Faculty of Applied Science and Engineering (FASE) during the 1920s and 1930s. The student records shed light on their socio-economic background, which they shared to a large extent with their male counterparts and the other women attending university at the time. The available sources also provide information on the school's curriculum and pedagogical practices, and on the main features of student life at FASE. The institution cultivated and transmitted a deeply masculine culture: to train an engineer was to train a man and to construct a specific type of masculinity, symbolized by the "Schoolmen" and the "School Spirit." How did the pioneers adapt to this environment? How did FASE respond to their arrival? The article accounts for the diversity of views and experiences of the female students, and for the different reactions to their presence. Nevertheless, the entry of this pioneering group at FASE openly raised the question: can a woman be a woman and an engineer? Other studies are needed to better understand how female students answered this question in their own way, in different schools of engineering and in different historical settings. This work will help bring answers to this other question, which is still widely debated: why so few women engineers?